Application of Color Doppler Ultrasound to Identify and Repair Postoperative Cerebrospinal Fluid Leak: A Technical Note. Issue 1 (29th January 2022) - West, James L.; Abode-Iyamah, Kingsley; Chen, Selby G.; Fox, W. Christopher; Bydon, Mohamad; Miller, David A.; Clendenen, Steven R.
Abstract : BACKGROUND: Incidental durotomy is a known complication of spinal surgery. Persistent cerebrospinal fluid (CSF) leak after unrecognized durotomy may lead to prolonged hospitalization and significant morbidity. If initial bed rest fails, the surgeon must choose between nontargeted methods such as oversewing the wound and lumbar drain placement or return to the operating room. OBJECTIVE: To report the novel use of color flow doppler (CFD) in conjunction with ultrasound (US) to localize the point of CSF leak, assist with aspiration of the pseudomeningocele, and direct the application of fibrin sealant or epidural blood patch. METHODS: This article includes a description of the technique as a technical note. RESULTS: A 72-year-old man underwent L2-5 laminectomies for spinal stenosis. During the index operation, a durotomy occurred and was repaired primarily. The patient subsequently developed leg weakness, back pain, and bulging of the incision. Using CFD, the site of durotomy was determined. Under direct visualization, 34 mL of CSF was aspirated from the pseudomeningocele and 20 mL of fibrin sealant was placed opposing the durotomy. At 2-month follow-up, CFD confirmed absent flow and MRI demonstrated pseudomeningocele resolution. CONCLUSION: This article represents the first report highlighting the utility of CFD US to guide epidural patch placement for postsurgical CSF leaks. CFD allows localization of the durotomy and direct application of blood or fibrin sealant, potentially increasing the success rate of epidural blood patch in postoperative patients. This approach is less invasive than revision surgery and does not require the prolonged hospitalization of lumbar drainage or other nontargeted interventions.